A Test of the Cox, Ingersoll, and Ross Model of the Term Structure - Gibbons, Michael R.; Ramaswamy, Krishna (Review of Financial Studies, 1993)
We test the theory of the term structure of indexed-bond prices due to Cox, Ingersoll, and Ross (CIR). The econometric method uses Hansen’s generalized method of moments and exploits the probability distribution of the single-state variable in CIR’s model, thus avoiding the use of aggregate consumption data. It enables us to estimate a continuous-time model based on discretely sampled data. The tests indicate that CIR’s model for index bonds performs reasonably well when confronted with short-term Treasury-bill returns. The estimates indicate that term premiums are positive and that yield curves can take several shapes. However, the fitted model does poorly in explaining the serial correlation in real Treasury-bill returns.